Evaluasi Kualitas Sistem Informasi Pergudangan pada Perusahaan Distributor Obat-Obatan Menggunakan Model McCall - Wicaksono, Soetam Rizky; Setiawan, Rudy; Purnomo, Purnomo; Nurwegiono, Muhammad (Universitas Merdeka Malang, 2024)
This research was conducted to evaluate the quality of the warehouse information system at a pharmaceutical distribution company in order to provide recommendations regarding system upgrade decisions. Considering the importance of the effectiveness of the warehouse system in maintaining stock accuracy and the smooth distribution of pharmaceuticals, this evaluation uses the McCall Model, which includes the aspects of Product Operation, Product Revision, and Product Transition. The method used involved in-depth interviews with four warehouse staff and two managers who provided deep insights into the strengths and weaknesses of the current system. The interview results indicate that although the system is satisfactory in operational aspects such as data accuracy, reliability, efficiency, integrity, and ease of use, there is significant dissatisfaction regarding maintenance capabilities, flexibility, portability, reusability, and interoperability. While the managers are quite satisfied with the revision aspects, the majority of warehouse staff expressed challenges in system maintenance and adaptation. The biggest issues were found in the system's ability to transition between operational environments, be reused in other applications, and communicate with other systems. This study concludes that improvements are needed in the aspects of maintenance and flexibility, as well as enhanced system integration to meet dynamic operational needs. Suggestions for future research include involving more respondents from various divisions and using additional methods such as quantitative surveys and direct observation to obtain a more comprehensive picture.